The Link Between Employees’ Sense of Vitality and Proactivity: Investigating the Moderating Role of Personal Fear of Invalidity - Wörtler, Burkhard; Van Yperen, Nico W.; Mascareño, Jesús M.; Barelds, Dick P. H. (Frontiers in Psychology, 2020)
Proactive behavior has emerged as a key component in contemporary views of individual work performance. Hence, a central question in the literature is how to enhance employees’ proactive behavior. We investigated whether the more that employees experience a sense of vitality (i.e., energizing positive affect), the more likely they are to show proactive behavior at work, and whether this applies only to employees with a low personal fear of invalidity [(PFI) i.e., the inclination to be apprehensive about the risks/negative consequences of making errors]. Experimental (N = 354) and cross-sectional field (N = 85) studies provided consistent evidence for a positive relation between employees’ sense of vitality at work and their self-rated proactivity. The predicted moderation effect was observed only for manager-rated proactivity. We conclude that feeling energized in the workplace is not necessarily associated with observable proactive behavior. It is only when employees experiencing a sense of vitality at work are not prone to fearing the risks/negative consequences of making errors that they are more likely to show observable proactive behavior in an organization.